Incidencia del crecimiento económico sobre el índice de alfabetización digital en Ecuador: Un análisis de datos panel, durante el periodo 2009-2019 - Ramón Rodríguez, Jandry Javier (2023)
A large part of the population, about 54.5%, still does not have access to the Internet and even more the urban area has a lower rate of digital illiteracy than the rural area. Therefore, the main objective of this research is to evaluate the relationship between the digital literacy index and economic growth in Ecuador, during the period 2009-2019, through a panel data analysis in order to know the relationship between variables and suggest mechanisms for improvement. Therefore, data were collected from the Instituto Nacional de Estadísticas y Censos [INEC] and from the Banco Central del Ecuador [BCE] data from 2009 to 2019, to demonstrate the relationship between variables through panel data models. As a result of the methodology, economic growth does not contribute significantly to the digital literacy index. However, income and age were positive for the model. Thus, it is recommended that government policy implications should invest more in adequate infrastructure and thus place technological tools. This would benefit the human capital to specialize with an added value and use it as an instrument to develop and grow the Ecuadorian economy.